Grasping the Agent’s Perspective: A Kinematics Investigation of Linguistic Perspective in Italian and German - Gianelli, Claudia; Marzocchi, Michele; Borghi, Anna M. (Frontiers in Psychology, 2017)
Every day, we primarily experience actions as agents, by having a concrete perspective on our actions, their means and goals. This peculiar perspective is what allows us to successfully plan and execute our actions in a dense social environment. Nevertheless, in this environment actions are also perceived from an observer’s perspective. Adopting such a perspective helps us to understand and respond to other’s people actions and their outcomes. Importantly, similar experiences of being agent and observer occur also when actions are not physically acted/perceived but are merely linguistically shared. In this paper we present two exploratory studies, one in Italian and one in German, in which we applied a direct comparison of three singular perspectives in combination with different verb categories. First, second and third person pronouns were combined with action and interaction verbs, i.e. verbs implying an interaction with an object – e.g. grasp - or an interaction with an object and another person – e.g. give. By means of kinematics recording, we analyzed participants’ reaching-grasping responses to a mouse while they were presented with the different combinations of linguistic stimuli (pronouns and verb type). Results of Experiment 1 on reaching show that, when they are preceded by YOU, interaction verbs reached the velocity peak earlier than action verbs, since a further motor act will follow. Thus pronouns influence perspective taking and while comprehending language we are sensitive to the motor chain organization of verbs. The absence of the same effects in Experiment 2 is likely due to the fact that, being the pronoun in German mandatory, it is perceived as less salient than in Italian. Overall our results supports the idea that language is grounded in the motor system in a flexible way, and highlight the need for cross-linguistic studies in the field of embodied language processing.